Возникновение арочного эффекта в сборных многопустотных плитах и его влияние на НДС главных ригелей плоского сборно-монолитного перекрытия - Савицкий, Н. В.; Зезюков, Д. М. (Видавництво Національного університету "Львівська політехніка", 2010)
Подано інформацію про НДС середніх ригелів плоского збірно-монолітного перекриття при виникненні у багатопорожнинних плитах арочного ефекту. Occurrence of arch effect in modular multihollow plates and its influence on tensely deformed condition of the main crossbars stressedly-deformed beams state of simple flat-slab precast and cast-in-situdeck.
Keywords: арочний ефект; НДС головних ригелів; arch effect; tensely deformed condition of the main crossbars